The Effect of Product Quality and Price Perception on Purchase Decision-Making Process Mediated by Brand Image in EdTech Start-Up - Astrid Nurul Azizah; Syti Sarah Maesaroh; Asep Nuryadin (LP2M IAIN Palopo, 2025)
The quick development of digital technology has changed consumer behavior and sped up the expansion of Indonesian educational technology (EdTech) platforms. Among these, one of the digital training platforms is crucial for enhancing digital proficiency. With brand image acting as a mediating variable, this study attempts to investigate how product quality and price perception affect the decision to buy. 205 respondents, who were both participants and alumni of Dibimbing's bootcamp programs, participated in a quantitative study that used a convenience sample strategy. The findings reveal that the purchase decision-making process is positively and significantly impacted by both price perception (β = 0.214; p < 0.000) and product quality (β = 0.397; p < 0.000). Moreover, The impacts of Price Perception (indirect effect β = 0.123; p < 0.000) and Product Quality (indirect effect β = 0.183; p < 0.000) on the Purchase Decision-Making Process are considerably mediated by Brand Image. The direct effect of Product Quality remains stronger than the mediated one, suggesting that perceived quality is the dominant factor influencing purchasing behavior in EdTech contexts. These results highlight the strategic importance of enhancing product quality, implementing value-driven pricing, and strengthening brand image through testimonials and digital innovation to improve users’ purchasing decisions